Flooding scenarios due to land subsidence and sea‐level rise: a case study for Lipari Island (Italy). (February 2017) - Anzidei, Marco; Bosman, Alessandro; Carluccio, Roberto; Casalbore, Daniele; D'Ajello Caracciolo, Francesca; Esposito, Alessandra; Nicolosi, Iacopo; Pietrantonio, Grazia; Vecchio, Antonio; Carmisciano, Cosmo; Chiappini, Massimo; Chiocci, Francesco Latino; et al.
Abstract: Archaeological and instrumental data indicate that the southern sector of the volcanic island of Lipari has been subsiding for the last 2100 years due to isostatic and tectonic factors, at variable rates of up to 11 mm a −1 . Based on this data, a detailed marine flooding scenario for 2100 AD is provided for the bay of Marina Lunga in the eastern part of the island from (1) an ultra‐high‐resolution Digital Terrain and Marine Model (DTMM) generated from multibeam bathymetry (MB) and Unmanned Aerial Vehicles (UAV), (2) the rate of land subsidence from Global Positioning System (GPS) data and (3) the regional sea‐level projections of the International Panel on Climate Change (IPCC). When land subsidence is considered, the upper bound of sea‐level rise is estimated at 1.36 m and 1.60 m for RCP4.5 and RCP8.5 climate change scenarios, respectively. Here, we show the expected impact of marine flooding at Lipari for the next 85 years and discuss the hazard implications for the population living along the shore.